Education for All : The Cost of Accessibility - Steinfeld, Edward (World Bank, Washington, DC, 2012)
The goal of Education for All (EFA) is to provide universal access to primary education throughout the world. To accomplish this goal, as many as 10 million classrooms will be built in developing countries by 2015. A key objective of the program is to ensure that no child is denied access to education because of disability. Access to all schools is necessary to ensure that children with disabilities can participate independently in a mainstreamed environment since most villages will have only one school building. The related construction costs, if any, are not a barrier to providing access and are insignificant when compared to the benefits. Children who are educated with their peers have greater opportunities to become productive members of their societies and be more integrated socially in their communities.